2017
DOI: 10.1016/j.mam.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoprotective mechanisms for specialized pro-resolving mediators in the resolution of lung inflammation

Abstract: Bronchi are exposed daily to irritants, microbes and allergens as well as extremes of temperature and acid. The airway mucosal epithelium plays a pivotal role as a sentinel, releasing alarmins when danger is encountered. To maintain homeostasis, an elaborate counter-regulatory network of signals and cellular effector mechanisms are needed. Specialized pro-resolving mediators (SPMs) are chemical mediators that enact resolution programs in response to injury, infection or allergy. SPMs are enzymatically derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 122 publications
(206 reference statements)
0
39
0
Order By: Relevance
“…We have extended our previous investigation on lung injury in workers exposed to aerosols containing 80–85% nanoparticles of TiO 2 or Fe-oxides to nanocomposite researchers and we have shown that nanocomposites workers have high markers of oxidative stress in EBC [ 24 ]. In this study of researchers involved in various steps of nanocomposite synthesis and processing during the research and development phase, we have expanded our repertoire of biomarkers to also include several pro-inflammatory cytokines/chemokines (TNF, IL 5, and IL 9), as well as anti-inflammatory IL 4, IL 10, and IL 13, and lipoxins LXA4 and LXB4 [ 25 ] in EBC. These cytokines/chemokines stimulate the growth, differentiation, and recruitment of mast cells, eosinophils, basophils, and B-cells, all of which are involved in humoral immunity and allergic responses.…”
Section: Introductionmentioning
confidence: 99%
“…We have extended our previous investigation on lung injury in workers exposed to aerosols containing 80–85% nanoparticles of TiO 2 or Fe-oxides to nanocomposite researchers and we have shown that nanocomposites workers have high markers of oxidative stress in EBC [ 24 ]. In this study of researchers involved in various steps of nanocomposite synthesis and processing during the research and development phase, we have expanded our repertoire of biomarkers to also include several pro-inflammatory cytokines/chemokines (TNF, IL 5, and IL 9), as well as anti-inflammatory IL 4, IL 10, and IL 13, and lipoxins LXA4 and LXB4 [ 25 ] in EBC. These cytokines/chemokines stimulate the growth, differentiation, and recruitment of mast cells, eosinophils, basophils, and B-cells, all of which are involved in humoral immunity and allergic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Differently, no EBC markers were elevated in this study, and no positive trend was noted. Some elevations in our previous study concerned especially LTs, inflammation markers that may reflect subclinical inflammation in the respiratory system, as they are involved in the response to injury, infection, or allergy (27)(28)(29). Therefore, markers in EBC usually reflect occupational exposures of workers to nanomaterials by inhalation (30)(31)(32)(33)(34), including office employees exposed to nanoTiO 2 (35).…”
Section: Discussionmentioning
confidence: 95%
“…SPMs mainly act through binding to receptors in cell surface. Of note, eosinophils, neutrophils, mast cells and lung epithelial cells express SPM receptors being able to produce and respond to these molecules [120]. A proper resolution of inflammation assures the reduction of secretion of pro-inflammatory mediators and recruitment of granulocytes while increases clearance of apoptotic cells and induces tissue repair responses [119].…”
Section: Granulocyte-targeted Therapies For Asthmamentioning
confidence: 99%